FAKTOR-FAKTOR STORE ENVIRONMENT PEMBENTUK STORE IMAGE DAN PENGARUHNYA TERHADAP KEPUTUSAN PEMBELIAN PRIVATE LABEL DI MATAHARI DEPARTMENT STORE ROYAL PLAZA SURABAYA - Siti Shoimah (J-MACC, 2018)
This research aims to determine the Store Environment factors (Store Planning, Merchandising, Store Design and Visual Communications) that form the Store Image and its effect on Private Label Purchasing Decisions. Type of research is Explanatory Research. The sampling technique in this research used purposive sampling with a total sample of 102 respondents who were buyers of Nevada clothing at Matahari Department Store Royal Plaza Surabaya. According to factor analysis test it is known that there are 5 factors that build the Store Image: Store Atmosphere, Product Quality, Product Variety, Value for Money and Price. The Value for Money factor is the dominant factor influencing the decision to buy Nevada clothing at Matahari Department Store Royal Plaza Surabaya.